Accounting for CO2 emissions from international shipping: Burden sharing under different UNFCCC allocation options and regime scenarios - Nadine Heitmann; Setareh Khalilian (Kiel Institute for the World Economy (IfW), 2010)
CO2 emissions from international shipping, which are currently unregulated, are predicted to rise from 2.7% today to 18% in 2050. International bunker fuel emissions have been excluded from any commitment in the Kyoto Protocol; the UNFCCC conference in Copenhagen also failed to bring about clear directions on how to proceed with these emissions. In this paper we investigate the various options suggested by the Subsidiary Body for Scientific and Technological Advice (SBSTA) of the UNFCCC for allocating CO2 emissions from international shipping to individual countries. We discuss economic and regulatory issues related to these options and the consequences of applying them. We evaluate the various options on the basis of environmental effectiveness, possibility of legal implementation, and fairness of burden sharing. We conclude that an allocation of international shipping emissions should be conducted on the basis of the operating company.
Keywords: Q52; Q54; Q56; 330; climate change; international shipping; CO2 emissions; Schifffahrt; Kohlendioxid; Luftverunreinigung; Klimaveränderung; Prognose; Klimaschutz; Umweltabkommen; Welt